Sistem Informasi Inventaris Barang pada Fakultas Ilmu Sosial dan Ilmu Politik Universitas Syiah Kuala - Rahmatillah; Fathurrahmad; Ismail (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
The use of information technology has become a necessity in the modern era. The Faculty of Social and Political Sciences, Syiah Kuala University still uses a manual approach in collecting inventory data, which makes it difficult for staff to process data and make reports. To overcome this challenge, this research offers the development of a web-based Goods Inventory Information System using PHP and MySQL. Data collection methods include field studies and literature studies. This research aims to understand existing inventory information systems, design new systems, and explore user needs. Using a qualitative approach and case study method, this research analyzes the current system, designs improvement proposals, and implements them using the waterfall software development method. The result is an efficient and reliable inventory information system, which is expected to increase the effectiveness and efficiency of inventory management at the Faculty of Social and Political Sciences, Syiah Kuala University. This research highlights the importance of integrating information technology in academic institutional administration to improve performance and efficiency.